Educação musical escolar: um caminho a trilhar como disciplina eletiva em uma escola de ensino médio no município de Pacajus-CE - Paula, Genegleisson Queiroz de (2024)
The present research aims to contribute with a pedagogical proposal based on theoretical-methodological assumptions regarding musicalization to a high school in the city of Pacajus-CE. It is hoped that the proposal can support it in the daily educational practice in the teaching-learning process with Art. For this trajectory, the following procedural steps will be followed: At first, in the light of Bourdieu's assumptions (2009), we will try to elucidate the students' musical taste (cultural capital), estimate the sociocultural profile (fields) and analyze the students' expectations and previous experiences with music making (habitus). The second moment of this proposal will be of a bibliographic nature, in order to analyze theoretical supports and existing methodologies in relation to music teaching. To do so, we will use, above all, the writings of Professor John Dewey (1979), who in his works describes experience and education. Still at this point in the research, an analysis of music teaching will be drawn, starting from Conservatorial Education, Collective Teaching, Shared Musical Learning and active methodologies for music teaching, to which due to the profile of this work was meticulously accurate the choice of four important music educators, listed here in alphabetical order: Dalcroze, Edgar Willems, Kodály and Schafer. Having unveiled the investigative trajectory on the theoretical bases for the elaboration of a pedagogical proposal, we move on to the final step: the presentation of the pedagogical material.